Analysis of Mid-Semester Assessment Questions for Class XI Arabic at MAS Al-Islam Petala Bumi, Indragiri Hulu - Naqiyah, Neni; Handayani, Latifah; Basid, Abdul (Language Circle: Journal of Language and Literature, 2024)
Question Item Analysis is still very much needed by teachers to create quality measuring instruments for learning outcomes and provide real measuring results. This research aims to analyze validity, reliability, level of difficulty, distinguishing power, and distracting power. The method used in this research is descriptive quantitative. The data source in this research is the student answer sheets in the mid-semester assessment of class XI Arabic in MAS Al-Islam, Petala Bumi, Indragiri Hulu 2022-2023 school year. Data was collected using documentation and analyzed using the ANATES program. The results of this research include 1) Validity: 36% of questions are valid and 64% are invalid. 2) Reliability: reliability coefficient value 0.20 (low reliability). 3) Difficulty level: 56% difficult questions, 44% medium questions, and 0% easy questions. 4) Differentiation power: 20% of questions are very good, 0% of questions are good, 36% of questions are fair, 28% of questions are bad, and 16% of questions are very bad. 5) Distracting power: 6% of questions are very good, 28% of questions are good, 44% of questions are fair, 20% of questions are bad, and 2% of questions are very bad. The mid-semester assessment questions for Arabic class